Research in personnel and human resources management. Vol. 32 - Buckley, M. Ronald; Halbesleben, Jonathon R. B.; Wheeler, Anthony R. (Research in personnel and human resources management., 2014)
Volume 32 of Research in personnel and human resources management (RPHRM) contains seven papers on important issues in the field of human resources management. The subject matter in this volume covers myriad areas: compensation, performance evaluation, reputation, employee furloughs, and research methodology.